Reanalysis of the Tilt MTFs Based on the C-Band Empirical Geophysical Model Function - Zhang, Yanmin; Wang, Yunhua; Zhang, Jie; Liu, Yingzhe (IEEE geoscience and remote sensing letters, 2021)
The tilt modulation is one of the key factors affecting sea wave inversion accuracy based on some microwave sensors such as SAR, microwave spectrometer, and so on. Up to now, the traditional tilt modulation-transfer functions (MTFs) based on the Bragg scattering model and Phillips spectrum have been used in the sea wave spectrum retrieval algorithm for microwave sensors operating at medium incident angles. The traditional tilt MTFs are only related to radar polarization and incident angle, but not affected by wind speed and wind direction. However, the values of the tilt MTFs evaluated on the basis of the C-band empirical geophysical model function (GMF) CMOD5.na demonstrate that wind speed and wind direction also have significant effects on the tilt MTFs. In addition, the comparisons show that the values of the traditional tilt MTFs for both HH (horizontal) and VV (vertical) polarization cases are obviously smaller, which indicates that the traditional tilt MTFs would underestimate the influence of the local incident angle change on the scattering fields. On the other hand, the difference between the horizontal and the vertical polarization tilt MTFs, however, is overestimated by the traditional tilt MTFs. Finally, by fitting the data evaluated based on the C-band empirical GMF, we propose new tilt MTFs, which can overcome the shortcomings of the traditional tilt MTFs.